2015
DOI: 10.3201/eid2111.150271
|View full text |Cite
|
Sign up to set email alerts
|

RmtC and RmtF 16S rRNA Methyltransferase in NDM-1–ProducingPseudomonas aeruginosa

Abstract: We investigated 16S rRNA methyltransferases in 38 blaNDM-1–positive Pseudomonas aeruginosa isolates and found RmtC in 3 isolates, 1 of which also harbored RmtF. The isolates were clonally unrelated; rmtC and rmtF genes were located on a chromosome with the blaNDM-1 gene. Strategies are needed to limit the spread of such isolates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 12 publications
2
20
1
Order By: Relevance
“…In our study, we characterized five different types of 16S rRNA methyltransferase genes responsible for aminoglycoside nonsusceptibility. Among these, rmtC was found to be the most predominant type in the northeastern part of India, which is unusual compared to the findings of other studies (2). These aminoglycoside resistance determinants were found to be associated with broad-host-range plasmids of diverse incompatibility groups, reflecting multiple sources of acquisition through lateral gene transfer.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…In our study, we characterized five different types of 16S rRNA methyltransferase genes responsible for aminoglycoside nonsusceptibility. Among these, rmtC was found to be the most predominant type in the northeastern part of India, which is unusual compared to the findings of other studies (2). These aminoglycoside resistance determinants were found to be associated with broad-host-range plasmids of diverse incompatibility groups, reflecting multiple sources of acquisition through lateral gene transfer.…”
Section: Discussioncontrasting
confidence: 43%
“…rmtH, and npmA) have been detected in various nosocomial pathogens (2). Organisms harboring 16S rRNA methyltransferases along with extended-spectrum ␤-lactamases (ESBLs) and carbapenem resistance determinants have mostly been reported (3,4).…”
mentioning
confidence: 99%
“…Among these, rmtB (16.39%) was found to be the most predominant type in this part of India, on the contrary, Wangkheimayum J et al, (2017) found Rmt C being predominant in the Eastern part of the India (8). It is reported that 16S rRNA methyltransferases often coexist with bla NDM and bla CTX-M genes (20) (8) and our study was not an exception. The findings that ESBL producing uropathogens co-harbored carbapenem, aminoglycoside and AmpC resistant genes underscore that India as an epicenter of horizontal transfers of high-level resistance alleles between Gram-negative bacteria irrespective of community or nosocomial settings [17] [18].…”
Section: Resultssupporting
confidence: 47%
“…The rmtA gene in P. aeruginosa carries a mobile element Tn5041 [58,59] identified previously in Enterobacteriaceae [56], while the rmtB gene identified in Serratia marcescens is located in the flanking of Tn3-like region responsible for multiple antimicrobial resistance [59,60], and both methyltransferases and mobile elements are present in P. aeruginosa ( Table 2). The rmtC and rmtF genes ( Table 2) might have been acquired from plasmids as part of mobile genetic elements and finally integrated and stabilized on the chromosome [61]. The rmtG gene ( Table 2) is likely located in the chromosome [62].…”
Section: Rrna Methyltransferases Associated With Aminoglycoside Resismentioning
confidence: 99%